Reevaluating factors associated with negative attitudes toward police: capturing information from college students - Armstrong, James (Journal of ethnicity in criminal justice, 2021)
While a significant amount of research has been conducted in regards to public opinion of police, limited information can be found that reflects college students' opinions toward the subject, and even fewer studies have specifically used students on a college campus as a sample to study such opinions. The majority of past research focuses on low-income minorities who live in transitional neighborhoods and those who typically harbor the most negative views of the police in the United States. The questions this study attempted to answer were, "Are there certain demographic and social factors that can predict negative views toward police?" "If so, do these factors differ from or continue to confirm the results presented in past studies?" This study, through the use of questionnaire survey research, seeks to determine if a broader demographic of individuals, particularly college students, might be dissatisfied with police in present times, in light of the recent events regarding police use of force, what some may call police brutality, hostility, and unprofessionalism. The dependent factor was the respondents' views toward police. A two-part questionnaire survey was distributed to a sample of 323 students at a mid-size university in a southwestern state, and the data obtained from the surveys were analyzed to determine what additional demographic variables may be significant in the explanation of negative attitudes toward the police. Race and ethnicity remained a significant variable and "single" was found to be an unusual significant variable that was seldom used in prior research.